2020
DOI: 10.1109/access.2020.2999369
|View full text |Cite
|
Sign up to set email alerts
|

A Dual-Band Omnidirectional Circular Polarized Antenna Using Composite Right/Left-Handed Transmission Line With Rectangular Slits for Unmanned Aerial Vehicle Applications

Abstract: A dual-band omnidirectional circularly polarized (CP) antenna using composite right/lefthanded (CRLH) transmission line (TL) with miniaturized size is presented. The antenna consists of a circular radiation patch and a circular ground connected by three copper shorting vias, on which three rectangular slits are etched. Two sets of opposite branches are arranged in sequence around the radiation patch and ground to widen the impedance bandwidth (BW). The zeroth-order resonance (ZOR) structure by CRLH-TL and mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 21 publications
(19 reference statements)
0
20
1
Order By: Relevance
“…It is found that the architecture of the EZR-MZR resonators array is some kind like the alford loop. 17,18,[22][23][24] The alford loops are utilized to excited CP mode in a dielectric resonator, 22 and to radiate horizontal field omni-directionally. 23,24 It must be pointed out that the operating mechanisms of our proposed antenna is different from the alford loop.…”
Section: Discussion On the Operating Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…It is found that the architecture of the EZR-MZR resonators array is some kind like the alford loop. 17,18,[22][23][24] The alford loops are utilized to excited CP mode in a dielectric resonator, 22 and to radiate horizontal field omni-directionally. 23,24 It must be pointed out that the operating mechanisms of our proposed antenna is different from the alford loop.…”
Section: Discussion On the Operating Mechanismmentioning
confidence: 99%
“…A side view of the resonator is presented at the upper half of the Figure 1B. It is found that the architecture of the EZR‐MZR resonators array is some kind like the alford loop 17,18,22‐24 . The alford loops are utilized to excited CP mode in a dielectric resonator, 22 and to radiate horizontal field omni‐directionally 23,24 .…”
Section: Impedance Bandwidth Enhancement For Ezr‐mzr Based Antennamentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative method in analyzing the circular polarization behavior of this structure is explained as follows, which is based on the comparison of the E-field and surface current at each moment valid for omni-directional antennas, as described in [38].The E-field on the radiating plane mainly contributes to the vertically-polarized waves at the end-fire direction of the antenna. Similarly, the current surface on the radiating plane introduces the horizontally-polarized waves at the horizontal xy-plane of the antenna.…”
Section: Circular Polarizationmentioning
confidence: 99%
“…Thus, in an increasingly technological and volatile world, the need to update organizational paradigms becomes evident [20]. Reacting and adapting instantly to the population's behavioral changes is essential for providing quality public service [17].…”
Section: Introductionmentioning
confidence: 99%